2021
DOI: 10.1111/jog.15036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perinatal outcomes between controlled‐release dinoprostone vaginal delivery system (PROPESS) and metreurynter for cervical ripening in labor induction: A retrospective single‐center study in Japan

Abstract: Aim: This study aimed to compare the efficacy and safety of a controlled-release dinoprostone vaginal delivery system (PROPESS) and a metreurynter for labor induction. Methods: This retrospective case-controlled study included 117 pregnant women (51 and 66 in the PROPESS and metreurynter groups, respectively) who required labor induction after >37 weeks' gestation at Mie University Hospital between January 2018 and September 2020. The primary outcome was the success rate of vaginal delivery. The secondary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, only a few studies to date have reported the factors affecting the clinical efficacy of PROPESS in Japanese pregnant women. 2,5 Despite its clinical effectiveness, wide variability in the efficacy of dinoprostone has been noted among pregnant women. 6 Maternal age, gestational age, parity, and vaginal pH could influence the efficacy of dinoprostone in cervical ripening and labor induction/delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, only a few studies to date have reported the factors affecting the clinical efficacy of PROPESS in Japanese pregnant women. 2,5 Despite its clinical effectiveness, wide variability in the efficacy of dinoprostone has been noted among pregnant women. 6 Maternal age, gestational age, parity, and vaginal pH could influence the efficacy of dinoprostone in cervical ripening and labor induction/delivery.…”
Section: Introductionmentioning
confidence: 99%
“…PROPESS was at last approved by the Japan Ministry of Health, Labor, and Welfare in January 2020, and is the only choice for pharmacologic cervical ripening in Japan. Therefore, only a few studies to date have reported the factors affecting the clinical efficacy of PROPESS in Japanese pregnant women 2,5 …”
Section: Introductionmentioning
confidence: 99%
“…Factors increasing a chance for effective labour induction using the insert include younger age, white and Asian race, a lower body mass index (BMI), multiparity, older gestational age, a condition post water breaking, and a greater cervical maturity according to Bishop's score [20]. The use of dinoprostone increases the percentage of natural childbirths versus mechanical methods, especially in primigravida women [21]. Other management regimes are also verified when dinoprostone proves to be ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have compared the mechanical methods of ripening and PGs [1,3,5], and since its introduction in Japan, there have been several reports on CR-DVI [6][7][8][9][10]. However, it has only been a short time since its introduction in Japan, and it cannot be said that it has been fully investigated.…”
Section: Introductionmentioning
confidence: 99%